National and international criminal jurisdiction over United Nations peacekeeping personnel for gender-based crimes against women - O'Brien, Melanie (2010)
This thesis seeks to determine the most effective jurisdiction for criminal accountability for UN peacekeeping personnel who engage in sexual exploitation and abuse of women, and other conduct amounting to violence against women. As criminalisation is sought as the appropriate method of prevention and punishment of such conduct, it is first examined why criminalisation is necessary. The impact of sexual exploitation and abuse (SEA) on women in the territories in which peace operations are located is detailed as harms in the form of violations of the rights of these women. Alternatives to criminal sanctions are then considered, in particular the actions of the UN towards prevention and prohibition of SEA. While such regulations are necessary, they are ultimately inadequate in preventing and punishing SEA. Included is an assessment of the Draft Convention on Criminal Accountability of UN Officials and Experts on Mission, the adoption of which would support criminalisation. However, the UN itself is unable to exercise criminal jurisdiction, and thus it is essential to examine which jurisdictions would be most effective in undertaking criminal prosecution of peacekeeping personnel. The choice between national jurisdictions and international criminal justice is debated. Which jurisdiction offers a more effectual forum for ensuring accountability? What potential impediments exist and how can such hindrances can be overcome? This thesis argues that gender-based crimes by UN peacekeepers should be criminalised, and that, while the International Criminal Court should not be discounted as a potential forum for prosecuting perpetrators, domestic prosecutions are far more likely and far more effective.